PANEL ANALIZA UTICAJA MAKROEKONOMSKIH POKAZATELJA NA POSLOVANJE FINANSIJSKIH INSTITUCIJA U REPUBLICI SRBIJI - Račić, Željko; Ercegovac, Dajana; Milić, Dragana (International Journal of Economic Practice and Policy, 2022)
This paper aims to estimate the impact of macroeconomic indicators (gross domestic product - GDP, inflation rate and industrial production index) on liquidity, profitability and solvency of financial institutions in the Republic of Serbia. The research is based on applying a dynamic GMM panel model, while the results of the application of static panel models were analyzed as the control results. The research results support the assumption that the growth of GDP and inflation rates affects the increase of financial institutions' profitability. Also, the estimation results implicate that the growth of GDP and the inflation rate is linked with the reduction of financial institutions' liquidity, while the growth of industrial production rate affects its increase. Finally, the results of the study indicate that GDP growth has an influence on the rise of financial sector solvency. This comparative analysis using panel data models is relevant to a broad range of researchers and policymakers interested in macroeconomic relations and the financial sector.
Keywords: macroeconomic indicators; financial institutions performance; static panel data models; dynamic panel data models